Comparison of Cryotherapy Performed With Ice or Gel and Superficial Skin Cooling of Older Women: A Randomized, Crossover, Clinical Trial - Fachin K.D.S.M. (2024)
© 2024 Lippincott Williams and Wilkins. All rights reserved.Background and Purpose: Cryotherapy is an affordable and popular treatment of soft tissue injuries, which can reduce inflammation and pain. Studies have specifically addressed young adults and athletes, and these findings have been extended to older adults in clinical practice. Aging is associated with changes in the skin, including collagen degradation, decreased fat layer thickness, and reduced blood flow, which can alter the skin response to stress. Because of age-related changes, there are concerns about the direct use of ice on the skin of older individuals. Skin injuries were also observed after cryotherapy. This study aimed to assess the most effective and safe cryotherapy for superficial skin cooling among older women. Methods: Eighteen older women were enrolled in this blinded, randomized, crossover, clinical trial. The mean values (SD) of their age, height, and weight were 70.0 years (6.0), 156.0 cm (9.1), and 72.8 kg (19.5), respectively. The participants underwent cryotherapy using bagged ice, bagged ice plus a wet towel, or gel pack for 20 minutes. The surface temperature of the skin was measured at the end of a 20-minute cryotherapy session using an infrared thermometer. Repeated-measures analysis of variance was conducted to analyze the effect of cryotherapy modalities and time, as well as the interaction between these 2 factors. The secondary outcome was the presence of cryotherapy-induced lesions. Results and Discussion: Cryotherapy modalities had significant effects on superficial skin temperature (P =.001). Time points after application also had an effect (P <.0001), and no interaction was observed between cryotherapy modalities and time points (P =.051). Bonferroni post hoc evaluation showed that bagged ice (P =.008) and gel (P =.007) were more effective in decreasing the superficial skin temperature than bagged ice plus wet towel. No difference was observed between bagged ice and gel (P =.32). Three of the 18 patients experienced adverse effects with the gel pack. Conclusion: This study of older women found that ice and gel cooled the skin more effectively than ice wrapped in towels. However, the gel pack had some adverse effects. Therefore, bagged ice is recommended for cryotherapy in older women.